Identification of Enolase as the Target of 2-Aminothiazoles in Mycobacterium tuberculosis - Heather H. Wescott (Frontiers in Microbiology, 2018)
Tuberculosis is a massive global burden and Mycobacterium tuberculosis is increasingly resistant to first- and second-line drugs. There is an acute need for new anti-mycobacterial drugs with novel targets. We previously evaluated a series of 2-aminothiazoles with activity against Mycobacterium tuberculosis. In this study, we identify the glycolytic enzyme enolase as the target of these molecules using pull down studies. We demonstrate that modulation of the level of enolase expression affects sensitivity to 2-aminothiazoles; increased expression leads to resistance while decreased protein levels increase sensitivity. Exposure to 2-aminothiazoles results in increased levels of metabolites preceding the action of enolase in the glycolytic pathway and decreased ATP levels. We demonstrate that 2-aminothiazoles inhibit the activity of the human α-enolase, which could also account for the cytotoxicity of some of those molecules. If selectivity for the bacterial enzyme over the human enzyme could be achieved, enolase would represent an attractive target for M. tuberculosis drug discovery and development efforts.